Incidence of bullying in schools: A study of a cross-section of primary and secondary school students in Brunei Darussalam - Veloo, Palanisamy K. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This paper consolidates the findings of two studies conducted in Brunei Darussalam on the incidences of bullying among Primary and Secondary school pupils. Students from both Primary and Secondary schools responded to a questionnaire on the incidence of bullying in their school. Results from the studies show that the frequency of the incident of bullying peaked at around secondary one and showed a decline in the upper forms. While the ranking of the types of bullying experienced by students at the different levels of schooling were similar, differences were noted in the ranking of the types of bullying experienced by boys and girls particularly in the primary years. Psychological bullying was more common among girls whereas bullying of a physical nature was more common among boys. The classroom was the place where students‟ experienced most bullying and a close friend and parent were the individuals to whom most students would report the incidence of bullying. Some implications for classroom practice and further research are discussed.